Antiphospholipid Syndrome Associated with Nonradiographic Axial Spondyloarthritis - Jozélio Freire De Carvalho; Antoniella Fernanda Mendanha Sousa (Case Reports in Rheumatology)
Herein, we describe a patient with antiphospholipid syndrome (APS) associated with nonradiographic axial spondyloarthritis (NRAS). A 31-year-old woman with a past medical history of uveitis experienced a pulmonary thromboembolism in March 2014 and was treated with rivaroxaban (20 mg/day). Five months later, she started complaining of low back pain. The results on contrast-enhanced sacroiliac magnetic resonance imaging were normal. Laboratory tests revealed positive HLA-B27 and the presence of lupus anticoagulant and IgM anticardiolipin. The diagnoses of APS and NRAS were made. The patient was treated with rivaroxaban for APS and sulfasalazine (2 g/day), respectively. As she showed the presence of lupus anticoagulant antibodies in blood, she did not receive nonsteroidal anti-inflammatory drugs. After 6 months, the patient was asymptomatic, without lumbar pain; she also showed normalization of the erythrocyte sedimentation rate and the C-reactive protein and vitamin D levels, good control of lumbar pain, and no new uveitis episodes. The APS was also stable. To the best of our knowledge, this is the first reported case of NRAS associated with APS.